Seasonal variation in Proximate composition of Nine Freshwater Fish - Paul, Baidya Nath; Bhowmick, Sadrupa; Singh, Puja; Chanda, Soumen; Sridhar, Narasimhan; Giri, Shiba Shankar (Indian Journal of Animal Nutrition, 2019)
The variation in proximate composition was determined in relation to season and body weight of some freshwater fish i.e. Mystus vittatus, Ompok bimaculatus, Channa striata, Wallago attu and Pangasianodon hypophthalmus, Labeo bata, Labeo calbasu, Cirrhinus reba and Puntius javanicus. The samples were collected at different seasons from different places and were grouped as small (g) and big (g). Nutritional composition of fish species were analyzed during the three seasons i.e. Q1(January-April), Q2(May-August) and Q3 (September-December). Protein content ranged from 12.52-19.19(%) among the species studied on fresh weight basis. Protein content was significantly higher (P100g) during January-April. Protein, fat and ash content of P. javanicus was significantly higher (P100g) during (September-December). Protein content was significantly higher (P